Description Of Nutrition Status Of Bride And Groom Based On Level Knowledge Of The First 1000 Days Of Life In Cimanggis Depok - Nadira Nurarifah; Titus Priyo Harjatmo (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
The First Thousand Days of Life, which is 270 days during pregnancy and 730 days in the first life of the baby, is a sensitive period because the problems that arise are permanent. The biggest problem that occurs in children is stunting (37.2%). In addition, one factor that supports the nutritional status of women of childbearing age who still experience Chronic Energy (20.8%). The best approach is to prepare the bridge and groom's nutritional status and increase knowledge about the First 1000 Days of Life. The purpose of this study is to determine the description of nutritional status of prospective brides based on knowledge about the First 1000 Days of Life. This research use qualitative method with cross sectional design with sampling accidental sampling within 1 week with result of 21 bride candidate. Result of nutritional status of bride candidate is normal (85,7%), while for knowledge about 1000 First Day of Life included in enough category (57,1%). Suggestion for the office of religious affairs is that on pre-marriage counseling is given material about the First 1000 Days of Life. Some extension materials about the motto of the card to healthy, calcium-containing foods and the suggestion to consume tablets added blood.